KEGIATAN PENGAJARAN KEPADA ANAK – ANAK DI SAAJA (SEKOLAH ALTERNATIF ANAK JALANAN ) - Azeharie, Suzy Suzanna; Fauziek, Catherine; Azizah, Tarisha Wardah; Jinda, Shiyam; Albansyah, Raihan; Putri Andini, Nur Kholizah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2024)
Having the courage to immediately take action is not easy, community development activities through institutions are focused on efforts to help lower class people who have an interest and desire to work together in groups, identify needs, and carry out joint activities to meet their needs. The issue of many young people getting a decent education, not knowing basic knowledge, prompted this Community Service Activity (PKM) by implementing it from the end of early September to the beginning of October to choose to teach at the Alternative School for Street Children (SAAJA), aiming to help and increase young generation and receive proper education for all groups. PKM activities are carried out using fun methods starting from group gymnastics, coloring, learning the alphabet, demonstrating animal sounds and movements, going into the field to play to get to know the environment and plants more deeply, holding competitions in groups so that younger siblings understand the importance of cooperation and thinking. The method presented is more interesting than usual so that children stay focused and participate in learning with a happy heart. The method used is proven to bring changes to the younger siblings who are taught, starting from attitudes and behavior that are more ambitious, younger siblings who respond more well and are curious about things around them.